Development and Preliminary Evaluation of a New Real‐Time RT‐PCR Assay For Detection of Peste des petits Ruminants Virus Genome. Issue 3 (19th July 2013) - Polci, A.; Cosseddu, G. M.; Ancora, M.; Pinoni, C.; El Harrak, M.; Sebhatu, T. T.; Ghebremeskel, E.; Sghaier, S.; Lelli, R.; Monaco, F.
Summary: A duplex real‐time reverse transcription‐polymerase chain reaction (qRT‐PCR) assay was developed for a simple and rapid diagnosis of Peste des petits ruminants (PPR). qRT‐PCR primers and TaqMan probe were designed on a conserved region of nucleocapsid protein (Np) of PPR virus (PPRV) genome. An in vitro transcript of the target region was constructed and tested to determine analytical sensitivity. Commercial heterologous Armored RNA ® was used as an internal positive control (IPC) for either RNA isolation or RT‐PCR steps. The detection limit of the newly designed duplex real‐time RT‐PCR (qRT‐PCR PPR_Np) was approximately 20 copies/ μ l with a 95% probability. No amplification signals were recorded when the qRT‐PCR PPR_Np was applied to viruses closely related or clinically similar to PPRV‐ or to PPR‐negative blood samples. A preliminary evaluation of the diagnostic performance was carried out by testing a group of 43 clinical specimens collected from distinct geographic areas of Africa and Middle East. qRT‐PCR PPR_Np showed higher sensitivity than the conventional gel‐based RT‐PCR assays, which have been used as reference standards. Internal positive control made it possible to identify the occurrence of 5 false‐negative results caused by the amplification failure, thus improving the accuracy of PPRV detection.